Comorbidity, age, and mortality among adults treated intensively for acute myeloid leukemia (AML). Issue 1 (January 2016) - Tawfik, Bernard; Pardee, Timothy S.; Isom, Scott; Sliesoraitis, Sarunas; Winter, Allison; Lawrence, Julia; Powell, Bayard L.; Klepin, Heidi D.
Abstract: Introduction: Our goal was to characterize comorbidities among adults receiving intensive therapy for AML, and investigate their association with outcomes. Methods: We retrospectively analyzed 277 consecutive patients with newly diagnosed AML treated intensively at the Comprehensive Cancer Center of Wake Forest University from 2002 to 2009. Pretreatment comorbidities were identified by ICD-9 codes and chart review. Comorbidity burden (modified Charlson Comorbidity Index [CCI]) and specific conditions were analyzed individually. Outcomes were overall survival (OS), remission, and 30-day mortality. Covariates included age, gender, cytogenetic characteristics, hemoglobin, white cell count, lactate dehydrogenase, body mass index, and insurance type. Cox proportional hazards models were used to evaluate OS; logistic regression was used for remission and 30-day mortality. Results: In this series, 144 patients were ≥ 60 years old (median age 70 years, median survival 8.7 months) and 133 were < 60 years (median age 47 years, median survival 23.1 months). Older patients had a higher comorbidity burden (CCI ≥ 1 58% versus 26%, P < 0.001). Prevalent comorbid conditions differed by age (diabetes 19.2% versus 7.5%; cardiovascular disease 12.5% versus 4.5%, for older versus younger patients, respectively). The CCI was not independently associated with OS or 30-day mortality in either age group. Among older patients, diabetes was associated with higher 30-day mortality (33.3% vs. 12.0% in diabetic vs. non-diabetic patients, p = 0.006). Controlling for age, cytogenetic characteristics and other comorbidities, the presence of diabetes increased the odds of 30-day mortality by 4.9 (CI 1.6–15.2) times. Discussion: Diabetes is adversely associated with 30-day survival in older AML patients receiving intensive therapy.